PENDIDIKAN ISLAM SEBAGAI UPAYA MA’RIFATULLAH - Asep Abdul Aziz; Nurti Budiyanti Budiyanti; Nurwadjah Ahmad; Andewi Suhartini; Ari Prayoga Prayoga (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
Facing this modern era, ma'rifatullah is faced with increasingly complex life challenges. The reality of education also continues to experience severe moral degradation. The reason is one of them is due to the shifting of part of human thought from virtuous life orientation to the pursuit of hedonic and materialistic lifestyles. The purpose of this research is to uncover and analyze a synergistic approach that can revive human interest in opening and studying the values of ma'rifatullah and the space to apply them especially in Islamic education referring to the Koran and Hadith. The method to be used is the study of literature. The type of data used is secondary data with literature study data collection techniques. Based on the findings and analysis in this study, namely; firstly, ma'rifatullah is the main goal of developing all human potential, when a human manifests his spiritual power, then easily deliver it to ma'rifatullah. Second, the educational implications of this concept include the goals, roles, functions, principles, educators, students, material, methods and educational media. All of that must have a positive influence on the mind and heart in increasing all the potential possessed by humans. Thus, all the educational components are directed towards ma'rifatullāh.